Pengaruh Kombinasi Amelioran Vinasse dan Pupuk Kalium Terhadap Pertumbuhan dan Pigmen Warna Daun Aglaonema sp. - Utami, Rahma Tri; Saputro, Nurcahyo Widyodaru; Agustini, Rika Yayu (JURNAL AGROPLASMA, 2024)
Vinasse is an ameliorant that can improve the chemical and physical properties of soil, but its use needs to be combined with inorganic fertilizer. One fertilizer can be used is potassium fertilizer which can increase the growth and colour pigment of Aglaonema sp. This research aims to obtain the best combination of Ameliorant Vinasse and Potassium fertilizer on the growth and leaf colour piment of Agalonema sp. This research on screen house at Campakasari Village, Campaka District, Purwakarta Regency, West Java from February 2024 to April 2024. The method used was a single-factor Randomized Block Design (RBD) with 8 treatments and 4 replications, resulting 32 experimental units consisting of: A (Control KCl 300kg/ha), B (Control Vinasse 10ml/l), C (Vinasse 10ml/l + KCl 200kg/ha), D (Vinasse 10ml/l + KCl 300kg/ha), E (Vinasse 10ml/l + KCl 400kg/ha), F (Vinasse 20ml/l + KCl 200kg/ha), G (Vinasse 20ml/l + KCl 300kg/ha), H (Vinasse 20ml/l + KCl 400kg/ha). The experimental result will be tested with an F-test, and if significant, will be further tested with Duncan Multiple Range Test (DMRT) at the 5% level. The method for leaf colour pigments uses questionnaire data scoring and analysed using multiple linear regression. The result showed that treatments significant affected on the growth and leaf colour pigment of Aglaonema sp. Treatment F (Vinasse 20 ml/l + KCl 200 kg/ha) give the highest yield for plant height(38,8 cm), number of leaves (9,50 leaves), number of shoots (2,25 shoots) and provides a strong correlation regression the visual appearance of leaf colour pigment and supporting factors of Aglaonema sp. on cosumer interest. Keywords: aglaonema sp., ameliorant vinasse, potassium fertilizer